A Critical Praxis: Narrowing the Gap Between Identity, Theory, and Practice. Issue 1 (31st March 2016) - Waller, Laurel; Wethers, Kinsey; De Costa, Peter I.
Abstract : Praxis is the balance of pedagogical theory and practice. This literature review explores praxis from a critical lens in terms of identity for both students and teachers. The authors center their framework on Hawkins and Norton's (2009) five principles for critical language teaching. The first principle relates to the situated nature of the program and practices, which involves contextualizing the plot and the characters of the classroom. Second, responsiveness to learners encourages teachers to identify students' multiple identities and allow them to experiment with these. Third, dialogic engagement is the discussion of identity in the classroom. Fourth, reflexivity requires teachers to examine their practices and the ideologies that guide their beliefs about second language acquisition and learning. Fifth, praxis combines all of these elements to create and harmonize a critical classroom. The article ends with a call for teacher training that incorporates these principles to better assist English language learners.